Reproductive health interventions for Inuit youth in the north: a scoping review - Hannah Mikhail; Sarah E. Kelly; Colleen M. Davison (BMC, 2021)
Abstract Background Inuit have thrived in the northern regions of Canada and Alaska for thousands of years. Recent evidence suggests that Inuit in this region have experienced systemic barriers to reproductive health with resulting disparities in reproductive health-related outcomes including those among youth. Northern youth-focused reproductive health intervention research or evaluations have not to date been well summarized. The objective of this scoping review was to summarize the literature over the past twenty years focusing on reproductive health interventions for adolescents in northern Inuit communities. Methods English-language articles from 2000 to 2020 were identified from seven scientific databases, a general internet search and a review of relevant websites. Two reviewers screened titles, abstracts and full texts and included articles if they mentioned a reproductive health intervention and pertained, directly or indirectly, to reproductive health for Inuit aged 10-19 in northern communities. Results Seventeen articles met the inclusion criteria, across six themes: (1) Barriers to reproductive health interventions in the north; (2) Northern midwifery; (3) Northern birthing centres; (4) Fetal fibronectin tests for identifying high-risk pregnancies; (5) Prenatal education classes; and (6) Interventions to improve access to and quality of reproductive health supports. Conclusion Overall there is relatively limited evidence base specific to reproductive health interventions and northern Inuit youth. What does exist largely focuses on maternal health interventions and is inclusive of but not specific to youth. There is some evidence that youth specific educational programs, participatory action research approaches and the promotion of northern birthing centres and midwifery can improve reproductive health for adolescents and young mothers in northern Inuit communities. Future initiatives should focus on the creation and evaluation of culturally relevant and youth specific interventions and increasing community and youth participation in intervention research for better reproductive health.